Handbook of herbs and spices. Volume 2 - Peter, K. V. (CRC Press ; Woodhead Pub., 2004)
Together with its companion volumes, Handbook of herbs and spices: Volume 2 provides a comprehensive and authoritative coverage of key herbs and spices. Chapters on individual plants cover such issues as description and classification, production, chemical structure and properties, potential health benefits, uses in food processing and quality issues.
Keywords: Herbs.; Spices.; Food industry and trade -- Quality control.; elektronické knihy; electronic books